Simultaneous Use of Alcohol and Electronic Nicotine Delivery Systems among College Students: Vaping History, Motivations for Use, and Outcome Expectancies. (10th February 2021) - Samuolis, Jessica; Morgan, Kerry D.; Greer, Anna E.; Diaz, Gabrielle; Elimanco, Kylie
Abstract: Introduction: Simultaneous polydrug use of electronic nicotine delivery systems (ENDS) and alcohol among college students is not well understood despite high rates of vaping and alcohol use among this population. The current study examined rates of simultaneous use and compared demographic characteristics, vaping history, motivations for initiating use, and outcome expectancies based on polydrug use status. Methods: An online and paper-and pencil questionnaire was administered to undergraduate students at a university in the northeast of the U.S. Purposive sampling strategies were used and a raffle was offered to incentivize participation. Results: Simultaneous polydrug use was prevalent in the sample of 670 college students, with 55.6% reporting simultaneous and non-simultaneous use, 34.0% reporting simultaneous use only, and 10.4% reporting non-simultaneous use only. An examination of differences based on polydrug use status indicated that students who reported simultaneous and non-simultaneous use were more likely to be males, report vaping daily, and endorse a wide range of motivations for use. Students who engaged in simultaneous use only were more likely to be females, indicate a social contextual-related motivation for initiating use, and had higher scores on appetite control, emotion regulation, and taste sensation outcome expectancies. Students who engaged in non-simultaneous use only were more likely to be nonwhite students and report the lowest expectation of health risks. Conclusions: The findings reveal differences based on simultaneous polydrug use status that can be informative in the development of contextually relevant prevention programming. Future research is needed to further explore simultaneous use of ENDS and alcohol.